2016
DOI: 10.1002/polb.24011
|View full text |Cite
|
Sign up to set email alerts
|

Design concepts for diffusive holographic photopolymers

Abstract: Diffusive photopolymers are an area of intense recent materials development, spurred by interest in holographic data storage, display holography, and custom diffractive optical elements, among other applications. This review examines a range of photopolymer formulations of academic and commercial interest, and places their design strategies in context via quantitative analysis of the recording fidelity, maximum refractive index change and the degree to which they achieve this limit. Finally, this analysis is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 131 publications
(161 reference statements)
1
28
0
5
Order By: Relevance
“…The Δn achieved F I G U R E 3 Diffraction efficiency curve of sample 1 measured at 632.8 nm (p-polarization) as function of the incidence angle with relative fit with the Kogelnik equation is of 0.0061, which corresponds to 35% of the formula limit. This result is consistent with the studies reported in the literature, 27,37 where it is shown that the usable fraction of Δn limit is between 30% and 60% for photopolymer formulations using CAB as binder. The diffraction efficiency was remeasured after 1 month without any apparent change, proving that the grating is stable in time, as also reported in a previous work.…”
Section: Vphg Writingsupporting
confidence: 93%
See 2 more Smart Citations
“…The Δn achieved F I G U R E 3 Diffraction efficiency curve of sample 1 measured at 632.8 nm (p-polarization) as function of the incidence angle with relative fit with the Kogelnik equation is of 0.0061, which corresponds to 35% of the formula limit. This result is consistent with the studies reported in the literature, 27,37 where it is shown that the usable fraction of Δn limit is between 30% and 60% for photopolymer formulations using CAB as binder. The diffraction efficiency was remeasured after 1 month without any apparent change, proving that the grating is stable in time, as also reported in a previous work.…”
Section: Vphg Writingsupporting
confidence: 93%
“…In order to predict the performances in terms of refractive index modulation (∆n) of a photopolymer system, the formula limit (Δ n limit ) 27 can be computed. It corresponds to the difference between the refractive index of the mixture ( n ave ) and the refractive index of the background material ( n 1 ): Δ n limit = n ave − n 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when diffusion is sufficiently fast that radicals can diffuse into the dark region of the fringe before terminating (R m * 1), the visibility of the radical distribution decreases inversely proportional to period squared. This behavior has previously been identified as the resolution limit in published materials [9]. This explains the observation that significant improvement in dynamic range can be achieved by increasing the termination rate via radical traps on the matrix [10].…”
Section: Photochemical Reactionsmentioning
confidence: 77%
“…Thereby a holographic grating with refractive index modulation (Δn) is gained finally (Figure 1). [5][6][7][8] Many kinds of cross-linked host matrices have been reported, which are a mixture of at least two active substances, such as epoxy-amine, epoxy-thiol, isocyanate-alcohol, orthoester-anhydride, and thiol-allyl. [9][10][11][12][13][14] Compared with other cross-linked systems, epoxy-amine has excellent mechanical properties and low volume shrinkage, which is very important for millimeter-thick media in holographic data storage.…”
Section: Introductionmentioning
confidence: 99%